2020
DOI: 10.2340/00015555-3683
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pruritus in Bullous Pemphigoid and Impact on Quality of Life: A Prospective Cohort Study

Abstract: Pruritus is a major symptom of bullous pemphigoid, but has been poorly studied. This study provides data on pruritus in bullous pemphigoid. Pruritus occurred daily in 85% of patients, with a mean pruritus intensity of 5.2/10. A majority of patients reported associated sensations, such as sensations of tingling, burning and pain. Patient's quality of life was greatly altered by pruritus. Dermatologists must take this observation into account and propose symptomatic treatments for pruritus if bullous pemphigoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Overall, our patients had moderate to severe disease according to the cut-off values of the BPDAI score defining the severity categories in BP ( 44 ), with a higher median BPDAI score than the cohort used to elaborate these cut-off values (53 and 37.5, respectively). In addition, our patients experienced severe pruritus with a mean PVAS of 7/10, whereas a recent series investigating pruritus and quality of life in BP described a mean pruritus intensity of 5.2/10 and showed that patients with a score above 5 had a greater alteration in their quality of life ( 45 ). As expected, our series included patients positive for anti-BP180 IgG (92%).…”
Section: Discussionmentioning
confidence: 53%
“…Overall, our patients had moderate to severe disease according to the cut-off values of the BPDAI score defining the severity categories in BP ( 44 ), with a higher median BPDAI score than the cohort used to elaborate these cut-off values (53 and 37.5, respectively). In addition, our patients experienced severe pruritus with a mean PVAS of 7/10, whereas a recent series investigating pruritus and quality of life in BP described a mean pruritus intensity of 5.2/10 and showed that patients with a score above 5 had a greater alteration in their quality of life ( 45 ). As expected, our series included patients positive for anti-BP180 IgG (92%).…”
Section: Discussionmentioning
confidence: 53%
“…Recently, two independent studies analyzed the clinical characteristics of pruritus in newly diagnosed BP patients. 5,18 In both studies, daily pruritus is experienced by more than 75% of cases with a mean pruritus intensity of 5-6 out of 10. In one study, half of the participants had already been treated with antipruritic agents, suggesting that the current treatments strategies for addressing pruritus in PD (e.g.…”
Section: Char Ac Teris Ti C S Of Pruritus In Pemphigoid Dis E a S E Smentioning
confidence: 90%
“…A second study investigated the role pruritus plays in QOL of 60 French BP patients using the 5-D Itch Scale and the ItchyQOL. 22 Results showed that 85% of patients experienced pruritus daily, at a mean severity of 5.2/10. Mean ItchyQOL score was 56.2/100 and 5-D Itchy scale score was 16.5/25 indicating significant QOL impairment due to pruritus which had not been specifically assessed previously.…”
Section: Pemphigoidmentioning
confidence: 98%
“…They found that OHIP-14 scores were higher in active patients with an average score of 42.28 ± 13.66 as compared to inactive patients with average scores of 29.08 ± 12.25. 22 Higher OHIP-14 scores correlated with pain scores. 23 This study may suggest oral health is a significant factor in the QOL of BP and PV patients, but large-scale conclusions were limited by response bias.…”
mentioning
confidence: 96%